Peripheral limb gangrene in a child with polyarteritis nodosa: An unusual presentation - Namrata Patil; Murtuja Shaikh; Alpana Kondekar; Surabhi Rathi; Karishma Bade; Suroor Makharia (Indian Journal of Rheumatology)
Polyarteritis nodosa (PAN) is a necrotizing vasculitis predominantly affecting medium-sized muscular arteries. PAN is comparatively rarer in childhood. It can present either in the form of cutaneous lesions (c-PAN) or systemic involvement (classic PAN). Classic PAN involves multiorgan system whereas cutaneous PAN has benign, chronic and relapsing course characterized by involvement of skin, muscles, and joints. PAN presenting as gangrene of peripheral limbs is a rare presentation. Very few cases have been reported in the Indian Pediatrics literature. Here, we report a case of peripheral limb gangrene presenting as the initial manifestation of PAN.